Low-energy consumption rapid synthesis of high-fluorescence nitrogen-doped carbon dots at room temperature using a combusted shrimp shell combined solution and application to catechins detection - Yi Chen Huang; Jun Yi Wu (Carbon Trends)
Shrimp shells are used as the carbon and nitrogen source to produce high-fluorescence nitrogen-carbon dots at room temperature by employing a cutting process based on NaCl crystals without added nitrogen-doped agents. The synthesis process is rapid (<5 min) and easy. The synthesized nitrogen-doped carbon dots (NCDs) are characterized using photoluminescence (PL) spectroscopy, transmission electron microscopy (TEM), scan electron microscopy (SEM), Fourier-transform infrared (FTIR) spectroscopy, and energy dispersive X-ray (EDX) analysis. The synthesized NCDs exhibit high fluorescence and are effectively used in the instant and fast detection of tea freshness.